ダイ37ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 1995-1996 - 神田, 啓史; カンダ, ヒロシ; Kanda, Hiroshi (1999)
P(論文) 本報告は第37次南極地域観測隊夏隊の行動の概要を示すものである。観測隊は56名で構成され, このうち越冬隊は藤井理行隊長兼越冬隊長, 川田邦男副隊長兼越冬副隊長を含む40名と夏隊は神田啓史副隊長兼夏隊長を含む16名, および2名のオブザーバーで編成された。1995年11月14日, 観測船「しらせ」により東京港を出発し, 12月14日, 氷海に入り, 24日に昭和基地に接岸した。夏期期間は, 昭和基地への物資輸送, 同基地での倉庫棟, 非常用発電棟の建設, 第9発電棟の解体, ドームふじ観測拠点への物資輸送などの作業を行った。とくに昭和基地およびS16への輸送品は総重量1069.5トンに及び, そのうち氷上輸送はこれまでに最も多い215.4トンであった。本格輸送の終了後は, 宗谷海岸露岩域での生物, 地学の野外調査, 基地観測では気球回収実験, 海洋物理の定常観測, テレメトリー観測等を実施した。越冬交代後はプリンスオラフ海岸での海底地形調査, 露岩域での野外調査, 続いてアムンゼン湾のリーセルラルセン山地域での調査を行った。帰路, 係留系ブイの回収を行い, 海洋定点観測をほぼ予定通り実施した。3月20日, シドニーに入港し, 27日, 日本に帰国した。 The summer activities in the 1995/1996 austral summer of the 37th Japanese Antarctic Research Expedition (JARE-37) are reported. The JARE-37 consisted of 16 members of the summer party, one news reporter and one graduate student. The Antarctic research vessel, SHIRASE, left Tokyo on 14th November 1995 and arrived at Fremantle, West Australia on 28th November. She reached the pack ice edge near Lutzow-Holm Bay on 14th December and anchored at Syowa Station on 24th December. Transportation of cargo by helicopter to Syowa Station and to the transport point (S16) for Dome Fuji Station was carried out between 16th December 1995 and 9th January 1996. A total of 1069.5 tons of cargo, including light oil transported by pipe and freight by oversnow vehicles, were transported. Construction to replace old buildings and facilities at Syowa Station were carried out. Main construction, a building for storage, continued throughout the summer at Syowa Station. In addition, an emergency power house and a seismographic hut were built, and the old power house was torn down. Summer research programs included a marine physical survey, atmospheric work, and field surveys in ice-free areas along the Soya Coast. All of the summer party left Syowa Station on 12th February and headed to Sydney, East Australia. En route, a geodesic survey, geological and biological research were carried out at ice-free areas along the Prince Olav Coast and oceanographic, marine biological observations, geomagnetism and ...